Daratumumab and Romiplostim Combined Therapy for a Long-Standing Refractory Primary Immune Thrombocytopenia – Case Report - Zoubi I; Warwar A; Perek S; Preis M (ImmunoTargets and Therapy)
Ibrahim Zoubi,1 Amir Warwar,1,2 Shoshan Perek,1 Meir Preis1,2 1Institute of Hematology, Lady Davis Carmel Medical Center, Haifa, Israel; 2Bruce and Ruth Rappaport Faculty of Medicine, Technion- Israel Institute of Technology, Haifa, IsraelCorrespondence: Meir Preis, Institute of Hematology, Lady Davis Carmel Medical Center, 7 Michal St, Haifa, Israel, Tel +972-4-8250445, Email Meirpr@clalit.org.ilAbstract: Multi-refractory immune thrombocytopenia (ITP) is not uncommon and associated with high morbidity and mortality rates. Although the precise mechanism of ITP is not yet fully understood, a therapeutic approach that relies on using a single agent in each treatment line may not be sufficient in this population. We report the case of a 67-year-old female with long-standing multi-refractory ITP treated with a combination of Daratumumab and Romiplostim who achieved a durable response for more than 42 weeks. Owing to the presentation of chronic and refractory disease, we used a dual-agent approach to address early immune destruction and promote megakaryocyte platelet production. Three doses of Daratumumab were administered during the induction phase (weeks 0,1,5) and then at less frequent intervals - every 4– 12 weeks for total of 4 doses during the maintenance phase. Romiplostim was administered weekly, with dose modification depending on the platelet count. We hypothesize that when combined with thrombopoietin receptor agonists (TPO-RAs), daratumumab administered at less frequent intervals over an extended period can be safely used, resulting in a prolonged response.Keywords: multi-refractory immune thrombocytopenia, anti CD38 directed therapy, TPO mimetic agents, case report